Aerodynamic and surface comparisons between Telstar 18 and Brazuca - Goff, J. E.; Hong, S.; Asai, T. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2018)
Aerodynamic coefficients were determined for Telstar 18 and Brazuca, match balls for the 2018 and 2014 World Cups, respectively. Experimental determination of aerodynamic coefficients prompted the development of computationally determined soccer ball trajectories for most launch speeds experienced in actual play. Although Telstar 18's horizontal range will be nearly 10% shorter than Brazuca's horizontal range for high-speed kicks, both Telstar 18 and Brazuca have similar knuckling effects due to nearly equal critical speeds and high-speed drag coefficients that differ by less than 10%. Surface comparisons suggest why aerodynamic properties for the two World Cup balls are so similar.